Optimized Blocking Of Porous Nitrocellulose Films For Sensitive Protein Microarrays. (April 2013) - Shultz, Michael A.; Ohdera, Aki; MacManiman, Jason; McGrath, Charles M.
Abstract: Super G Blocking Buffer was developed to produce low backgrounds in assays using nitrocellulose film-slides. Using this blocking reagent in combination with ONCYTE® SuperNOVA Film-Slides, we achieved an order of magnitude greater sensitivity in a cytokine microarray assay than with hydrogel- or silane-based glass substrates. Limit of detection (LOD) ranged from 160 – 690 fM for IL1α, IL1β, IL6, TNFα, TNFβ, and IFNγ without use of enzymatic signal amplification. The dynamic range for these microarrays on Film-Slides was greater than that of hydrogels and functionalized glass substrates and the LOD was 50-fold lower. On Film-Slides, the linear dynamic range spanned 6 orders of magnitude and the LOD was pushed into the zmole range (62.5 zmol). The advantages of Film-Slides are discussed in the larger context of developing the most sensitive protein microarrays for multiplexed clinical assays and quantitative studies of the cellular proteome.